Membangun Penjelasan dan Sikap Etis Trinitarian terhadap Kejahatan Natural COVID-19 - Sulistio, Thio Christian (Veritas : Jurnal Teologi dan Pelayanan, 2021)
Building Trinitarian Explanations and Ethical Attitudes Towards COVID-19 as Natural Evil. COVID-19 is a natural evil, namely an evil caused by a natural process that is not functioning properly because of the fall of humans into sins. The existence of COVID-19 as a natural evil will raise the question of why natural evil can exist, what is the purpose of natural evil, and how does this natural evil ends (the metaphysical problem of evil)? Another question is how the response or the attitude of the believers to the existence of this natural evil (the moral problem of evil)? The author tries to answer these two problems by using a trinitarian explanation of Christian metanarrative, namely from the point of God’s providence, the work of Jesus Christ on the cross, and the work of the Holy Spirit in the church. God in his sovereignty permits the natural evil of COVID-19 for the greater good. Jesus Christ, the Son of God, triumph over evil through His ministry on earth and on the cross. The Holy Spirit, sent by the Father and the Son, comforts and empowers the church to continues the mission of Jesus Christ.